Re-discovering Narratives of South African Defence Force Servicemen through the Informal Digital Archive (Journal of the Digital Humanities Association of Southern Africa, 2024)
The South African Defence Force (SADF) has become a point of contention in post-Apartheid South African public memory. From 1966 until 1989, approximately 600,000 white males were conscripted into the SADF to fight in conflicts around Southern Africa as well as at home in South Africa. While much academic work has been done on the SADF during the latter half of the Apartheid era, it is filled with rampant apologia relating to the actions of the SADF as well as the narratives of those that served within it. The stories and experiences of SADF conscripts and soldiers has essentially been ‘sanitized’ by academics and authors attempting to make them suitable for the post-Apartheid era. Yet, on internet forums and social media websites, many SADF veterans have found a space to express their narratives freely without the input of reconciliation conscious reviewers. In this informal digital space, a plethora of material has been deposited by these ex-servicemen which now serves as a digital archive from which researchers can gain valuable insight into the actions and experiences of SADF veterans. The unfiltered narratives found in this informal digital archive shines new light on the current academic understanding of the SADF. Instead of the narrative pushed by many academics and authors of young men filled with remorse for fighting a war they understood little about, this material tells a different story. White supremacism, braggadocio and light-hearted discussion on war crimes committed by the SADF fill these digital spaces, creating a counter-narrative to the apologetic stance of many historians and sociologists who have written extensively on the Border War. This paper will explore some of these informal digital archives and seek to answer not only why SADF veterans feel comfortable expressing their narratives freely in the digital space, but also why they have been largely ignored by mainstream academia.
Keywords: Archive; Forum; Media; SADF; Online